Relationship of Therupetic Communication with Caring Behavior of Nurses in the Inpatient Unit - Karo, Mestiana Br; Ginting, Amnita; Pakpahan, Rotua Elvina (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Therapeutic communication is a way to build therapeutic relationships, the communication carried out must show an attitude of mutual acceptance, trust and respect. Caring behavior is a caring attitude and behavior in treating others we serve with love which is very important in increasing patient satisfaction so that patients feel comfortable and are helped in a faster healing process, besides that it also prevents worse conditions for patients. This research aims to find out Is there a relationship between therapeutic communication and the caring behavior of nurses in the inpatient unit at Santa Elisabeth Hospital, Medan. The research method used was correlation with a cross sectional approach, the number of respondents was 100 people. The research results showed that the majority of respondents (61%) rated therapeutic communication as adequate, the majority's caring behavior (86%) as very good. The results of the Spearman Rank correlation test are 0.305, meaning that the two variables have a sufficient relationship, with a p-value of 0.002 (p<0.05), there is a significant relationship between therapeutic communication and the caring behavior of nurses in the inpatient unit at Santa Elisabeth Hospital, Medan. So it can be concluded that respondents felt that nurse communication was sufficient. Nurse therapeutic communication is very important to improve the caring behavior of nurses in every health service to provide services to improve the quality of nursing care. The results of this research can provide information and input for the hospital to create a program to improve the quality of nurse communication by creating a PIN name for each nurse, so that when they enter the room and take action the patient knows the nurse's name. As well as giving rewards to nurses who have good communication and caring in each room.